(untitled) (Research, Society and Development, 2022)
Modern dentistry seeks to incorporate less invasive methods in order to minimize pain and discomfort during and after dental interventions. Thus, photodynamic therapy in the area of ​​endodontics has been an excellent option for adjunctive treatment to procedures to aid in the disinfection of root canal systems. Therefore, the objective of this study was to review the literature regarding the action of photodynamic therapy as a method of controlling endodontic pain. A descriptive research, carried out from a careful survey of articles indexed in the Scielo, Pubmed, Bireme and Scopus databases, published from 2002 to 2021, in English, Portuguese and Spanish. Keywords were used alone or in combination with the Boolean descriptor “AND”. In view of its established antimicrobial effect, photodynamic therapy has also been shown to be effective in alleviating pain, perhaps due to the light emitted by the low-power laser, even in a collimated manner, through the glass fiber coupled to the tip. In view of all the efforts made for the construction of the present work, it can be inferred based on the authors that PDT constitutes a significant contribution to the use in endodontics as an additional therapy, presenting effectiveness in the control of pain of endodontic origin.